Efeitos de quantidades de água sobre cultura do feijão (Phaseolus vulgaris L.), em quatro sistemas de manejo do solo - CHAGAS, JOSE MAURO; GOMES, JOSÉ MAGALHÃES; VIEIRA, CLIBAS; ARAÚJO, GERALDO ANTONIO DE ANDRADE (Revista Ceres, 2015)
.